ERGID: An efficient routing protocol for emergency response Internet of Things. (September 2016) - Qiu, Tie; Lv, Yuan; Xia, Feng; Chen, Ning; Wan, Jiafu; Tolba, Amr
Abstract: In recent years, Internet of Things (IoT) has been applied to many different fields such as smart home, environmental monitoring and industrial control system, etc. Under the pressure of the continuous expansion of network scale, how to ensure the real-time emergency response ability during data transmission has become a challenging problem for researchers. In this paper, we propose a routing protocol for Emergency Response IoT based on Global Information Decision (ERGID) to improve the performances of reliable data transmission and efficient emergency response in IoT. Specifically, we design and realize a mechanism called Delay Iterative Method (DIM), which is based on delay estimation, to solve the problem of ignoring valid paths. Moreover, a forwarding strategy called Residual Energy Probability Choice (REPC) is proposed to balance the load of network by focusing on the residual energy of node. Simulation results and analysis show that ERGID outperforms EA-SPEED and SPEED in terms of end to end (E2E) delay, packet loss and energy consumption. Additionally, we also carry out some practical experiments with STM32W108 sensor nodes, and observe that ERGID can improve the real-time response ability of network.